Evaluation of Organ Dose following Radiotherapy of the Brain using Bio-Based Head Phantom Made From Soy-Lignin bonded Rhizophora spp. - Siti Hajar binti Zuber; Nurul Ab. Aziz Hashikin; Nor Hafizah Ishak; Nursyatina Abdul Raof; Mohd Fahmi Mohd Yusof; Mohd Zahri Abdul Aziz (BioResources)
The purpose of this work was to create and assess a bio-based head phantom made from bio-based resources for external beam radiotherapy dose planning and delivery in brain cancer. The custom-made head phantom was fabricated using Rhizophora spp. bonded with soy flour and lignin, and its potential as phantom material was evaluated in previous studies. Organs at risk and planning target volume were identified using the treatment planning system, which was guided by computed tomography raw images. Thermoluminescent dosimeters were placed into specific holes positioned throughout the head phantom following individual calibration. Head phantom was imaged, planned and irradiated by linear accelerator. The planned predicted doses by treatment planning system at the targeted volume and the organ at risk regions were obtained and compared with the dosimeter doses. The result revealed that the planning target volume and organ at risks were within the dose range calculated by the treatment planning system, except for lens, optic chiasm and brainstem. Verification of the treatment plans was implemented, and good agreement between measured values and those predicted by the treatment planning system was found. The custom-made, bio-based phantom’s preliminary results have proved to be a valuable tool for the treatment dose verification, demonstrating its prospective as potential phantom material for use in radiotherapy.